2019
DOI: 10.21203/rs.2.16290/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric Properties of Instrumented Postural Sway Measures Recorded in Community Settings in Independent Living Older Adults

Abstract: Background: In the last few decades, research related to balance in older adults has been conducted in lab-based settings. The lack of portability and high cost that is associated with the current gold standard methods to quantify body balance, limits their application to community settings such as independent living facilities. The purpose of the study was to examine the test-retest reliability and the convergent validity of static standing balance performance using an accelerometer device. Methods: A total o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The negative relationship between the postural sway in the ML direction and the ABC scale indicates that participants with more sway had less confidence in their ability to maintain their balance while performing several daily activities. Several studies also found similar results despite using various measures to quantify subjects' confidence in their balance when compared to the amount of postural sway [42,47].…”
Section: Biomed Research Internationalmentioning
confidence: 66%
See 1 more Smart Citation
“…The negative relationship between the postural sway in the ML direction and the ABC scale indicates that participants with more sway had less confidence in their ability to maintain their balance while performing several daily activities. Several studies also found similar results despite using various measures to quantify subjects' confidence in their balance when compared to the amount of postural sway [42,47].…”
Section: Biomed Research Internationalmentioning
confidence: 66%
“…Moreover, a recent study found that lateral postural sway measures were more closely related to participants' perceptual assessment of exercise difficulty compared to sagittal postural sway measures [6]. Several studies also indicated that the magnitude of postural sway in the ML direction has more reliability [7,[37][38][39][40][41][42] and was correlated with more physical [42] and self-reported measures [6] as well as number of future falls [34][35][36] compared to that in the AP direction. Several studies provided an explanation for that, where they indicated that the lateral sway has more variation due to the narrow support base while performing balance exercises compared to the sagittal sway, which may allow for greater reliability and more relationships with different measures [6,7].…”
Section: Biomed Research Internationalmentioning
confidence: 99%